The Concept of Wasathiyah KH. Abdullah Syafi'i: A Study of the Thinking and Empowerment of the Indonesian Islamic Community - Nurhaidah, Siti Nuri; Farhana, Nurfitria; Fauziah, Syifa; Majid, Dzamaksyarif Abdul; Sutiono, Sutiono (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2025)
This study aims to examines how the principles of moderation were formulated and practiced within the contexts of education, da'wah, and socio-economic movements in Jakarta and surrounding areas. Using a qualitative approach with content analysis, this study reviews primary and secondary literature, including biographies, institutional records, and scholarly writings related to KH Abdullah Syafi'i. The data were analyzed through thematic categorization, source triangulation, and interpretation of recurring moderation patterns in his thought and activities. The findings reveal that KH Abdullah Syafi'i implemented wasathiyah through three interrelated strategies: integrative education that balances religious and general sciences, community empowerment based on social justice and self-reliance, and institutional development for leadership regeneration. The study contributes practically by offering a contextual model for applying wasathiyah in Islamic education and community development in plural societies. However, the research is limited by its dependence on secondary literature, which may not fully capture the local nuances of KH Abdullah Syafi'i’s practical experiences. Future studies could expand by using field data or oral histories to validate and deepen these findings.